2021
DOI: 10.1111/jcmm.16875
|View full text |Cite
|
Sign up to set email alerts
|

Advanced therapeutic modalities in hepatocellular carcinoma: Novel insights

Abstract: Hepatocellular carcinoma (HCC), the most common type of liver cancer, is usually a latent and asymptomatic malignancy caused by different aetiologies, which is a result of various aberrant molecular heterogeneity and often diagnosed at advanced stages. The incidence and prevalence have significantly increased because of sedentary lifestyle, diabetes, chronic infection with hepatotropic viruses and exposure to aflatoxins. Due to advanced intra‐ or extrahepatic metastasis, recurrence is very common even after ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 107 publications
(192 reference statements)
0
8
0
Order By: Relevance
“… 23 However, most HCC patients are diagnosed at a late stage and the 5‐year survival of these patients is poor. 3 Previous studies reported the increased level of sCD155 in the serum of cancer patients, including in lung cancer, gastric cancer, colorectal cancer, etc. 14 However, serum sCD155 level has not been previously investigated in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 However, most HCC patients are diagnosed at a late stage and the 5‐year survival of these patients is poor. 3 Previous studies reported the increased level of sCD155 in the serum of cancer patients, including in lung cancer, gastric cancer, colorectal cancer, etc. 14 However, serum sCD155 level has not been previously investigated in HCC.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Additionally, many HCC patients are diagnosed at advanced stages due to the lack of specific biomarkers for early‐stage HCC and thus are not candidates for surgery, resulting in a 5‐year survival rate of <16%. 3 , 4 Therefore, identifying novel biomarkers for prognosis prediction and early diagnosis of HCC is critical.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these drugs often struggle to differentiate between target protein sub-types, whereas RNA can more easily target specific mRNA or other ncRNA ( 31 ). A wide range of novel HCC therapeutics, including RNAi have been developed over the last two decades, however, a cure is not a reality at present ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other HCC therapies include immunotherapy, immune-cell therapy, differentiation strategy and RNA interference (RNAi) ( 2 ). Despite these advances a cure is yet to be developed and to date survival time has only been modestly extended ( 3 ). Central to the problem of HCC management is that this cancer remains (largely) asymptomatic until it is very advanced ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with advanced tumors are offered different treatments, including systemic prescription-based therapies like sorafenib, regorafenib, and nivolumab to loco-regional ablation or resection [2][3][4]. Liver transplantation, immunotherapeutic and radionuclide-based approaches, and targeted molecular and gene therapy interventions are other advanced modalities [5,6]. However, the high rate of tumor recurrence after treatment has led to a growing interest in developing innovative therapeutic approaches [7].…”
Section: Introductionmentioning
confidence: 99%